Workplace bullying and its relationship with spiritual climate: a latent profile analysis - Huang, Rong; Ran, Xu; Tang, Chenxi; Wei, Yanlin (Frontiers in Psychology, 2025)
ObjectiveTo explore the group characteristics and heterogeneity of workplace bullying among standardized training of nurses, to find out the potential categories of workplace bullying, and to explore its relationship with spiritual climate, to more comprehensively understand the occupational environment and mental health of standardized training of nurses, and to provide theoretical basis for managers to develop effective intervention measures.MethodsThe multi-center cross-sectional study method and 648 nurses in eight Grade A hospitals in Sichuan province were selected using the Chinese negative behavior questionnaire and spiritual climate questionnaire. Latent profile analysis was used to identify the heterogeneity of workplace bullying among standardized training of nurses and to use multiple linear regression to explore the relationship between workplace bullying and spiritual climate.ResultsAccording to the results of potential profile analysis, standardized nurses can be divided into three potential categories: “severe workplace bullying group,” “no workplace bullying group” and “bad workplace situation group.” According to the general data of one-way ANOVA, age, average weekly working hours, love of nursing work, harmonious relationship with colleagues, and whether formal work before training were the main factors affecting training nurses’ feeling of bullying in the workplace (p < 0.05, p < 0.01). Multiple linear regression analysis showed a negative association between spiritual climate and workplace bullying, with lower workplace bullying scores and higher spiritual climate scores.ConclusionThe proportion of organizational dimensions and bad workplace situations is too high. Nursing managers and educators should pay attention to and analyze the causes of bullying of standardized training nurses, and take effective preventive measures to reduce the occurrence of workplace bullying. Bullying in the workplace affects the spiritual climate, so nursing managers should consider formulating relevant management plans from the organizational level to reduce the occurrence of bullying in the workplace and improve the spiritual climate of the department.